Agreement between the Continuous Medical Education Programs and Necessary Training Topics in the Field of Emergency Medicine - Afshin Amini; Mehrnoosh Haraghi; Hojjat Derakhshanfar; Majid Shojaee; Hossein Alimohammadi; Alireza Majidi; Kamran Heidari (طب اورژانس ایران, 2015)
Introduction: Currently, there is a lack of data on the agreement between the continuous medical education (CME) programs and the necessary training topics in the field of emergency medicine in Iran. The present study aimed to evaluate the mentioned agreement in CME programs held during 2010-2014, all over the country. Methods: In the present cross-sectional study, the data recorded regarding emergency medicine-related CME programs were extracted from continuous training database of the Ministry of Health. Then, 30 items from the most important topics taught in emergency medicine training were selected by 3 emergency medicine specialists. Subsequently, the agreement of the selected training topics and CME programs was evaluated regarding duration of training, annual changes, and efficiency. Results: During 2010-2014, a total of 10147 hours of CME programs were held in relation to emergency medicine topics in Iran, which were most frequently (1015 hours) related to surgical emergencies. The next most frequent emergency-related CME programs were in the fields of toxicology with 810 hours (8.0%), neurology with 700 hours (6.9%), pediatric emergencies with 695 hours (6.8%), internal medicine with 675 hours (6.7%), and cardiopulmonary resuscitation with 555 hours (5.5%). In addition, it was determined that none of the CME programs were in complete agreement with the expected standards. Cohen’s kappa test showed that the agreement between the current conditions of CME programs with the standard was only 46.7% (95% confidence interval: 40.9 – 52.55) which shows a weak agreement (p = 0.19). Conclusion: The findings of the present study show the weak agreement of the CME programs held in the field of emergency medicine with the expected standards.